Uczenie działań komunikacyjnych poprzez bezpośrednią instrukcję - Nowicka, Agnieszka (My University, 2008)
The article focuses on teaching and learning conversational actions in English as a FL in direct instruction based on the guided discovery observation of discourse models such as transcribed video discus-sions and conversations. The aim of the task is to develop students’ communicative awareness, which in turn allows them to find in dis-course those communicative actions which suit their communicative style and contribute to the development of their personal communicative competence. Discourse observation tasks are accompanied by project tasks such as classroom role plays and discussions and interviews with a foreigner in which students are expected to produce the observed communicative actions. The paper is based on a case study of one student’s performance in the selected two types of tasks, discourse observation tasks and an interview with a foreigner.
Keywords: analiza konwersacyjna; ukierunkowana obserwacja; dydaktyka języka angielskiego jako JO